Who is afraid of the Gods? Rethinking escapism in Nigerian dramatic literature - Oluwasuji, Olutoba Gboyega (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Escapism can mean different things to diverse sets of people in various fields of study. To some people, it can mean escape to reality, while some can denote it as an escape to entertainment or distraction from boredom. Escapism in this paper takes a different turn and adopts the term to identify how different decisions can be influenced in any socio-cultural setting. Using South Western Nigeria as a case study, this paper questions the possible interpretations of escapism and the extent to which leaders, especially, identify with them. This paper uses Ahmed Yerima's Sacred Mutters and Iyase to explore the issue of misinterpretation and human machination to escape punishment from the gods.